Spinal meningioma: relationship between degree of cord compression and outcome. (4th March 2017) - Davies, Simon; Gregson, Barbara; Mitchell, Patrick
Abstract: Background: The aim of this study was to find the relationships between the degree of cord compression as seen on MRIs with persisting cord atrophy after decompression and patient outcomes in spinal meningiomas. Method: We undertook a retrospective analysis of 31 patients' pre- and postoperative MRIs, preoperative functional status and their outcomes at follow-up. The following metrics were analysed; percentage cord area at maximum compression, percentage tumour occupancy and percentage cord occupancy. These were then compared with outcome as measured by the Nurick scale. Results: Of the 31 patients, 27 (87%) had thoracic meningiomas, 3 (10%) cervical and 1 (3%) cervicothoracic. The meningiomas were pathologically classified as grade 1 (29) or grade 2 (2) according to the WHO classification. The average remaining cord cross-sectional area was 61% of the estimated original value. The average tumour occupancy of the canal was 72%. The average cord occupancy of the spinal canal at maximum compression was 20%. No correlation between cord cross-section area and Nurick Scale was seen. On the postoperative scan, the average cord area had increased to 84%. No correlation was seen between this value and outcome. Conclusion: We found that cross-section area measurements on MRI scans have no obvious relationship with function before or after surgery. This is a base for future research into the mechanism of cord recovery and other compressive cord conditions.